1999
DOI: 10.1007/s004170050221
|View full text |Cite
|
Sign up to set email alerts
|

Immune-mediated retinopathy in a patient with stiff-man syndrome

Abstract: These findings suggest autoimmune retinopathy, mediated by anti-GAD65 autoantibodies as the underlying cause of visual loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…6 There are only rare ocular inflammatory findings described in the literature and, to our knowledge, there is no reported case of scleritis in SPS. 8,9 As stated earlier, there is one reported case of autoimmune retinopathy believed to be due to anti-GAD antibodies attacking the inner and outer plexiform layers of the retina in a patient with SPS. 8 Herein, we reported a case of anterior scleritis in a patient with stable GAD(+) SPS.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…6 There are only rare ocular inflammatory findings described in the literature and, to our knowledge, there is no reported case of scleritis in SPS. 8,9 As stated earlier, there is one reported case of autoimmune retinopathy believed to be due to anti-GAD antibodies attacking the inner and outer plexiform layers of the retina in a patient with SPS. 8 Herein, we reported a case of anterior scleritis in a patient with stable GAD(+) SPS.…”
Section: Discussionmentioning
confidence: 87%
“…There is only one reported case of immune-mediated retinopathy and one patient with eye-movement abnormalities. 8,9 Herein, we describe a patient with anterior scleritis and SPS.…”
Section: Introductionmentioning
confidence: 99%
“…12 Anti-GAD antibodies have been associated with stiff person syndrome (SPS), LADA, and other autoimmune diseases, including pernicious anaemia, vitiligo, Graves disease, Hashimoto thyroiditis, myasthenia gravis, and autoimmune adrenal failure. 13 There has been one prior case report of immunemediated retinopathy in a patient with SPS and anti-GAD antibodies. 13 It is possible that this patient harboured other anti-retinal antibodies similar to our patient.…”
Section: Discussionmentioning
confidence: 99%
“…13 There has been one prior case report of immunemediated retinopathy in a patient with SPS and anti-GAD antibodies. 13 It is possible that this patient harboured other anti-retinal antibodies similar to our patient. Whether anti-GAD antibodies play a direct role in retinal disease has yet to be elucidated, and whether they are pathogenic in SPS also is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Darnell and co-workers reported a patient with SPS who had an abnormal visual evoked potential that reverted to normal after treatment with benzodiazepines, suggestive of underlying central GABA-ergic dysfunction. 7 Steffen et al 15 reported a 32-year-old patient with central visual loss OU and electrophysiologic evidence of retinopathy. Immunofluorescence showed strong reactivity to the inner and outer plexiform layers at dilutions of 1:1000 with the patient's serum mediated by anti-GAD-65 antibodies.…”
Section: Discussionmentioning
confidence: 99%